Mechanical properties and morphology of nylon 12 composites reinforced with graphene flake. (1st June 2018) - Lu, Xuan; Jin, Yunxue
Abstract: A study was performed to determine the effect of the content of fillers on the mechanical properties of a nylon 12 matrix composite mixed with graphene flake. The reinforcement fillers were dispersed in nylon 12 matrix before filling in the mode. Scanning Electron Microscope (SEM) were used to observe the morphology characterizations of reinforced composites and mechanical properties were determined by conducting tensile test, hardness. It is note that mechanical performance increased by 49.7% in tensile strength, 35.8% in Young's modulus and even 362.6% in hardness than that of neat nylon 12 with the addition 2.5 wt% of graphene.